Effective Corporate Governance And Financial Reporting In Japan - Rahman, Khondaker Mizanur; Marc Bremer, Marc Bremer (Asian Academy of Management (AAM), 2016)
This paper examines corporate governance in Japan since the 1990s. Its focus includes financial reporting, a key part of good governance. It offers an overview of various legal, institutional, and stakeholder aspects of governance, followed by an investigation of Japanese accounting, disclosure, and reporting. The paper presumes that accurate financial reporting is a prerequisite for good corporate governance. Bad governance often follows from fraudulent financial reporting. The paper also considers the status of international financial reporting standards, the nature of fraudulent financial reporting, the all-too-common practice of window dressing in Japan, the liabilities of corporate audit board members and financial auditors. Our findings suggest that the existing high quality laws, codes, guidelines, and institutional arrangements do improve corporate governance. Yet in practice, the quality of corporate governance in Japan has not matched the quality of its codes and regulations. The paper discusses Japan's new corporate governance code. It concludes that this code is excellent, but that more needs to be done to improve financial reporting. Finally, a number of suggestions are offered to enhance corporate governance and reduce fraudulent reporting.